Analisis Teknis dan Ekonomi dalam Pemanfaatan Area Sekitar Anjungan Lepas Pantai di Laut Jawa untuk Memproduksi Listrik Hijau dengan Turbin Angin Lepas Pantai - Resistentio Vembre Franika; Mohammad Kholid Ridwan; Abram Perdana (Universitas Batanghari Jambi, 2023)
Green electricity production with offshore wind turbines is a potential option to increase renewable energy penetration in Indonesia. Indonesia's geographical condition which has 70 percent of the ocean makes the offshore wind turbines interesting for further research. In this study, the area of the ocean that will be used is Papa's offshore platform, which from an operational economic point of view has decreased so that it can be converted into an offshore sub-station for an electricity substation before being sent to a sub-station on land with distance of 40 km and sea depth of 35 m. The study begins with an analysis of the meteo data conditions of the area around the offshore platform which produces an average wind speed of 5.5 m/s (for a height of 119 meters) and the greatest frequency of wind directions from the East Southeast (ESE) direction. Furthermore, the wind farm analysis shows that the best wind farm direction with the Vestas V162-7.2 MW turbine is in the East Northeast (ENE) - West Southwest (WSW) direction with an energy generation potential of 141,656.9 MWh/year and a wake loss of 10% for a generating capacity of 100 .8MW. To determine the economy, an analysis was carried out using LCOE and NPV which resulted in a green electricity production value (LCOE) of 0.192/kWh and in determining investment feasibility an NPV analysis was carried out which produced a selling value of green electricity with an offshore wind turbine of 0.271/kWh.